2001
DOI: 10.1046/j.1365-2567.2001.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of products of the mouse decay‐accelerating factor (DAF) genes. Exploitation of a Daf1 knock‐out mouse and site‐specific monoclonal antibodies

Abstract: SUMMARYDecay-accelerating factor (DAF) is a membrane regulator of C3 activation that protects self cells from autologous complement attack. In humans, DAF is uniformly expressed as a glycosylphosphatidylinositol (GPI)-anchored molecule. In mice, both GPI-anchored and transmembraneanchored DAF proteins are produced, each of which can be derived from two different genes (Daf1 and Daf 2). In this report, we describe a Daf1 gene knock-out mouse arising as the ®rst product of a strategy for targeting one or both Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 59 publications
5
110
0
Order By: Relevance
“…These findings are consistent with the known tissue distribution patterns of CD55 and CD59 in the mouse kidney. Both proteins are highly expressed on vascular endothelial cells and, although they were detected by immunohistochemistry in the mouse glomeruli, CD55 and CD59 were minimally expressed, if at all, on proximal tubules of the mouse (29,30). Endothelial expression of CD55 is also known to be induced by inflammatory stimuli (31).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the known tissue distribution patterns of CD55 and CD59 in the mouse kidney. Both proteins are highly expressed on vascular endothelial cells and, although they were detected by immunohistochemistry in the mouse glomeruli, CD55 and CD59 were minimally expressed, if at all, on proximal tubules of the mouse (29,30). Endothelial expression of CD55 is also known to be induced by inflammatory stimuli (31).…”
Section: Discussionmentioning
confidence: 99%
“…Factor D (fD Ϫ/Ϫ , H-2 b ) mice were a gift from Y. Ma (Birmingham, AL). Mice deficient in the Daf1 gene (Daf1 Ϫ/Ϫ ) were produced by Lin and colleagues 17 as described and backcrossed for Ͼ13 generations to B6 mice. B6 mice do not reject B6 Daf1 Ϫ/Ϫ skin (data not shown), confirming congenicity.…”
Section: Micementioning
confidence: 99%
“…12,16,17 Briefly, MultiScreen ELISPOT plates (Millipore, Bedford, MA) were coated overnight with the capture antibodies for IFN-␥, IL-4, or IL-17 (BD Biosciences). After a blocking step, recipient spleen or T cells (0.2 to 1 ϫ 10 6 per well) were plated and incubated with spleen cell stimulators (400,000 per well) at 37°C, 5% CO 2 , for 24 hours.…”
Section: Elispot Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…These regulators are DAF, complement receptor-related protein-Y (Crry), and the membrane inhibitor of reactive lysis (CD59). In the mouse, two genes, Daf1 and Daf2, code for DAF protein (Spicer et al, 1995 glyco-phosphatidylinositol anchored and widely expressed in a distribution similar to that in humans, whereas DAF protein deriving from the Daf2 gene is predominantly transmembrane anchored and restricted in its expression to testis (Lin et al, 2001;Song et al, 1996;Spicer et al, 1995) and splenic dendritic cells (Lin et al, 2001). Previous studies have shown that DAF present in the kidney derives entirely from the Daf1 gene (Lin et al, 2001;Spicer et al, 1995) and that it is expressed at high levels in glomerular capillary walls (Lin et al, 2001).…”
mentioning
confidence: 99%